Meteoritic influence on sodium and potassium abundance in the lunar exosphere measured by LADEE. Issue 12 (25th June 2016) - Szalay, Jamey R.; Horányi, Mihály; Colaprete, Anthony; Sarantos, Menelaos
Abstract: The Lunar Atmosphere and Dust Environment Explorer (LADEE) orbited the Moon for approximately 6 months, taking data with the Lunar Dust Experiment (LDEX), Ultraviolet‐Visible Spectrometer (UVS), and Neutral Mass Spectrometer (NMS). Here we compare coincident LDEX measurements of meteoritic influx to exospheric column densities of Na and K derived by UVS. We report a strong correlation of exospheric potassium and meteoroid ejecta during the Geminids meteoroid shower, exhibiting a much stronger response than sodium. With the exception of the Geminids, we find a weak correlation between the sporadic meteoroid influx as measured by LDEX and exospheric density as measured by UVS. Key Points: Lunar exospheric potassium abundance is significantly enhanced during the Geminids, lasting 4–8 days after peak meteoroid flux Sodium and potassium undergo different evolutions in the lunar exosphere Weak correlation is found between sporadic meteoritic input and exospheric neutral abundance